2014
DOI: 10.1111/1365-2664.12350
|View full text |Cite
|
Sign up to set email alerts
|

Seed and seedling traits affecting critical life stage transitions and recruitment outcomes in dryland grasses

Abstract: Agriculture and Natural Resources, Browns Valley, CA 95918, USA Summary 1. Seeding native plants is a key management practice to counter land degradation across the globe, yet the majority of seeding efforts fail, limiting our ability to accelerate ecosystem recovery. 2. Recruitment requires transitions through several seed and seedling stages, some of which may have overriding influences on restoration outcomes. We lack, however, a general framework to understand and predict differences in these critical demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
157
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(171 citation statements)
references
References 56 publications
9
157
1
4
Order By: Relevance
“…There are limits to setting specific trait targets as knowledge of which traits drive fitness and performance along environmental gradients is still developing (Webb et al 2010). Recent work has highlighted the need to move beyond considering adult leaf and root traits to also assessing seed and seedling traits when considering the role of functional traits in restoration performance (Larson et al 2015). Assessment of multiple traits is likely to improve the ability of restoration practitioners to develop restoration that is more resilient to future environmental changes.…”
Section: Moving From Compositional To Functional Goals In a Changing mentioning
confidence: 99%
“…There are limits to setting specific trait targets as knowledge of which traits drive fitness and performance along environmental gradients is still developing (Webb et al 2010). Recent work has highlighted the need to move beyond considering adult leaf and root traits to also assessing seed and seedling traits when considering the role of functional traits in restoration performance (Larson et al 2015). Assessment of multiple traits is likely to improve the ability of restoration practitioners to develop restoration that is more resilient to future environmental changes.…”
Section: Moving From Compositional To Functional Goals In a Changing mentioning
confidence: 99%
“…Ecologically appropriate plant materials can conceivably play a role in their repair by virtue of specific functional traits they possess ( Jones et al, 2010). Indeed, plant functional traits are increasingly being used to inform restoration (Funk et al, 2008;Roberts et al, 2010;Clark et al, 2012;Larson et al, 2014). If functional traits that confer ecological fitness, i.e., the ability to establish, grow, and reproduce, can be identified, artificial selection for these traits may potentially lead to plant materials that are able to restore a degree of ecosystem functioning ( Jones and Monaco, 2009;Jones et al, 2010).…”
Section: More Effective Native Plant Materials For Functional Restoramentioning
confidence: 99%
“…The four key life transitions that make up seedling recruitment are germination, seedling emergence, seedling establishment to an autotrophic state, and seedling survival through the end of the first growing season (Fenner and Thompson, 2005). Of these, emergence has been shown to be the most important for rangeland species ( James et al, 2011;Larson et al, 2014). Thus, native plant materials with an improved ability to emerge, particularly in unfavorable soil environments, may increase the probability of successful seedling recruitment.…”
Section: Improved Seedling Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct seeding is inefficient in terms of the proportion of seeds that produce an established seedling; in arid ecosystems it is common for only 2-7 % of seeds to establish (Chambers, 2000;James et al, 2011;Larson et al, 2015), although the use of biochar has shown to increase these percentages (Drake et al, 2016). The early developmental life-stages of plants are usually more sensitive to environmental or edaphic constraints than the adult stages (Standish et al, 2012) and the transition from germinated seed to emerged seedling has been identified as the life-stage transition most limiting the success of direct seeding .…”
Section: Introductionmentioning
confidence: 99%